2021
DOI: 10.3390/ijerph18063119
|View full text |Cite
|
Sign up to set email alerts
|

Physical Sports Activities and Exercise Addiction during Lockdown in the Spanish Population

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has led to the paralysis of the worldwide economy caused by the population’s lockdown to stop the virus spreading, making it difficult to do exercise. The aim of this study is to analyse the commitment to and feeling of insecurity related to practising sport, sports habits and the profile of the Spanish population during lockdown according to the level of addiction to exercise. The sample consisted of 1019 subjects with a mean age of 35 years old. The variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 60 publications
1
9
0
7
Order By: Relevance
“…As mentioned above, several studies worldwide, such as those by Savarese et al [3], Muscogiuri et al [4], and Berengui et al [18], reported a greater intake of processed or hypercaloric products caused by the stress of confinement due to the COVID-19 pandemic. In addition, an international online study, with the majority of participants being women, also showed that the number of snacks between meals increased significantly during home confinement [25]; however, in our study, during post-confinement, it was observed that, regarding the intake of salty snacks, processed pastries and soft drinks on a weekly basis, the majority response was that these types of products were not consumed.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…As mentioned above, several studies worldwide, such as those by Savarese et al [3], Muscogiuri et al [4], and Berengui et al [18], reported a greater intake of processed or hypercaloric products caused by the stress of confinement due to the COVID-19 pandemic. In addition, an international online study, with the majority of participants being women, also showed that the number of snacks between meals increased significantly during home confinement [25]; however, in our study, during post-confinement, it was observed that, regarding the intake of salty snacks, processed pastries and soft drinks on a weekly basis, the majority response was that these types of products were not consumed.…”
Section: Discussionmentioning
confidence: 92%
“…The vast majority of the subjects had a face-to-face work modality, followed by the blended work modality. This could have a positive influence when it came to reducing the possible intake of hypercaloric foods because the prolonged stay at home could lead to anxiety and a lack of routine and, consequently, the increased consumption of this type of food as a way to relieve stress, as reflected in the studies by Savarese et al [3], Muscogiuri et al [4] and Berengui et al [18]. However, on the other hand, returning to face-to-face work prevented dedicating the recommended time to meals and their preparation processes; therefore, people consumed precooked and processed foods with scarce nutritional value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise addiction has been defined as a strong desire to exercise, becoming more important than other spheres of life, such as family, social relations, work, etc., and is characterized by the lack of control and maintenance of behaviour, despite the negative consequences, causing withdrawal symptoms when spending several days without exercising (Goodman, 1990;Hausenblas & Symons-Downs, 2002;Szabo, 1995Szabo, , 1998Szabo, , 2000Youngman & Simpson, 2014). Therefore, exercise addiction can be considered a real problem with a great impact, because it may lead to risky behaviours (Berengüí et al, 2021).…”
Section: Palabras Clavementioning
confidence: 99%
“…The results of a survey completed by 606 respondents from 132 countries indicated that squats, single-leg squats, push-ups, and lunges were the most commonly applied workouts during by athletes the COVID-19 quarantine period [1]. The COVID-19 pandemic has led to rapid changes in the traditional workout industry (from contact to noncontact workout settings) via online platforms and wearable devices [2]. Wearable sensors have the advantages of portability, suitability for indoor workouts, facilitation of large population analysis, and longitudinal tracking of motion data for patients with musculoskeletal pain [3].…”
Section: Introductionmentioning
confidence: 99%